Digital Transformation of Toddler Posyandu Services via an Android-Based Application - Harsono, Harsono; Mulyono, Mulyono; Rinayati, Rinayati (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Abstract: Posyandu Balita as a community-based health service holds an essential role in improving maternal and child health in Indonesia. Nevertheless, the dependency on manual documentation frequently causes delays in reporting immunization, incomplete records, and limited access for parents to monitor child growth. This study sought to design and assess an Android-based Posyandu Balita application by applying a Research and Development (R&D) model combined with the System Development Life Cycle (SDLC) approach. The development process covered several phases: needs analysis, system design, application construction, pilot implementation, and evaluation through the Technology Acceptance Model (TAM). The pilot, which involved 10 health cadres and 10 parents, revealed that the application reduced data loss, facilitated more accurate immunization tracking, and encouraged stronger parental involvement. Functional testing indicated that the main features—digital medical records, reminder notifications, and growth chart visualization—worked consistently as intended. Based on TAM analysis, perceived usefulness (PU) and perceived ease of use (PEOU) significantly shaped users’ behavioral intention to utilize the system (PU = 62%, PEOU = 58%). Moreover, the level of parental compliance in child health monitoring increased, where 85% of parents actively accessed the digital platform compared to only 40% before the trial. Overall, the results demonstrate that mobile health applications developed with user-centered approaches can improve the effectiveness and efficiency of community-based services. The Posyandu Balita application is a promising innovation to support Indonesia’s digital health transformation. Further research is required to examine large-scale implementation, integration with national health information systems, and strategies for long-term sustainability. Keywords: Community Health, Toddler Posyandu, Android-based Application, Mobile Health, Technology Acceptance Model, Digital Innovation